Last expression is missing + should be (A'+B)+(A+C')\( Y = [(AB')(A'C)]' \)
\( Y = (AB')' + (A'C)' \)
\( Y = (A'+B)(A+C') \)
Which is the same as you've got.
You're operating on expressions alone though, which is O.K, but could you type this "question" in it's entirety because something's missing.
Oops, yes you're right. I missed that one somehow.Last expression is missing + should be (A'+B)+(A+C')
Did you go wrong?Demorgan problem
(( AB') (A'C))' One broke bar recd (AB')' + (A'C)'
then broke the bar again and recd A'+B+A+C' A'+a =1 1+ other variables =1?
Book states answer is (A+B') ( A'+C)
Where did I go wrong?
by Luke James
by Jake Hertz
by Jake Hertz